Pandemic Preparedness in the Aged Care Sector: A systematic literature review - Jennifer Kosiol; Richard Olley; Tracey Silvester; Jo_Anne Vidal; Helen Cooper (ACHSM, 2023)
Infectious disease outbreaks in aged care services present challenges for consumers and staff. The vulnerability of users of aged care services and a lack of preparedness on the part of aged care services to manage the risk associated with viral disease transmission was particularly evident during the COVID-19 pandemic. We used the PRISMA Method to review the available literature systematically. This qualitative review of the literature on pandemic preparedness assessed eight high-quality research papers and identified themes that emerged to support aged care services in preparing for future pandemics. These articles provided insight into what aged care services require to increase their capacity to respond to communicable disease outbreaks. Four themes emerged from the literature reviewed: Staff Training and Development, Safety Culture, Creating a Safe Environment by planning for contingencies and Risk and Resource Management (including resourcing for Personal Protective Equipment (PPE), Leader Presence and Time Responses and Clear, Consistent Messaging) were the dominant themes in the literature. The researchers found that using guidelines and checklists is helpful but only if they are clear, not complex and do not take too long to read. Risk strategies in future must also focus on the resources required to protect staff, families, and consumers. This paper also provides recommendations that will allow aged care services to respond to future communicable disease outbreaks more effectively. Such measures include the need for a planning methodology that incorporates ready access to PPE, the use of meaningful communication, increased hazard and risk awareness and the need to create a safety culture within the service based on sound values, attitudes and behaviours of leaders and staff.